2021
DOI: 10.1002/anbr.202000061
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of MicroRNAs into Primary Cells Using Nanostraw Technology

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that play key roles in posttranscriptional gene regulation. Being involved in regulating virtually all cellular processes, from proliferation and differentiation to migration and apoptosis, they have emerged as important epigenetic players. While most interest has gone into which miRNAs are involved in specific cellular processes or pathologies, the dosage‐dependent effects of miRNAs remain vastly unexplored. Different doses of miRNAs can cause selective downregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Whereas previous studies using nanostraws have used centrifugation or magnetic forces to direct cells to nanostraws, 3,5,17,23 the present method offers an alternative method to direct cells towards the substrate, not requiring any centrifugation step, cell concentration or cell modication. The method can be useful when fewer cells are available to work with, such as when working with circulating tumor cells and antigen specic T cells, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies using nanostraws have used centrifugation or magnetic forces to direct cells to nanostraws, 3,5,17,23 the present method offers an alternative method to direct cells towards the substrate, not requiring any centrifugation step, cell concentration or cell modication. The method can be useful when fewer cells are available to work with, such as when working with circulating tumor cells and antigen specic T cells, for example.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA can be detected by translocation of the probe into the cell through the deformation of the cell’s own plasma membrane during endocytosis. Pop et al designed another miRNA detection method employing a nanostraw-based electroporation delivery platform 122 . As shown in Fig.…”
Section: Fluorescence Sensingmentioning
confidence: 99%
“…Pretreating the surface can reduce the potential cytotoxicity of nanostructures to certain sensitive primary cell types. Pop and Almquist found that the nanostructures were harmful specifically when culturing primary basal keratinocytes on-chip without additional treatments . Cell viability significantly increased by adding a fetal bovine serum coating, which reduced membrane perturbations caused by the nanoscale protrusions.…”
Section: Technological Improvementsmentioning
confidence: 99%
“…Experiments with different dosages revealed that the delivery of frequent, low-concentration doses is preferable to a single large dose, as the continuous approach maintained a comparable response while requiring 22% less siRNA . RNAi has also been used with microscale EP to deliver miR-181a into cells to promote fibroblast proliferation . Additionally, microscale EP was effective in the delivery of cell penetrating peptides conjugated to peptide nucleic acids (CPP-PNAs) into macrophages infected with bacteria .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation